Transition to advanced market economies * Opening address * Opening lecture - Straszak, Andrzej (1931– ); Stefanski, Jacek; Owsinski, Jan (Instytut Badań Systemowych. Polska Akademia Nauk, 1992)
Hanna Gronkiewicz-Waltz, Janusz Lewandowski
19-22 pages ; 21 cm
Bibliography p. --0